Designing an integrated, nurse-driven and home-based digital intervention to improve insulin management in under-resourced settings. (October 2021) - Ngassa Piotie, Patrick; Wood, Paola; Webb, Elizabeth M.; Hugo, Johannes F.M.; Rheeder, Paul
Background: In South Africa, initiating insulin for people with type 2 diabetes and subsequent titration is a major challenge for the resource-constrained healthcare system. Inadequate support systems in primary care, including not being able to access blood glucose monitors and test strips for self-monitoring of blood glucose, results in patients with type 2 diabetes being referred to higher levels of care. In primary care, initiation of insulin may be delayed due to a shortage of healthcare workers. The delayed initiation of insulin is also exacerbated by the reported resistance of both healthcare providers and people with type 2 diabetes to start insulin. In South Africa, telehealth provides an opportunity to overcome these challenges and manage insulin therapy in primary care. Methods: We describe the development of a digital health intervention including the framework used, the theoretical approach and subsequent implementation strategies. Results: This intervention is an innovative, nurse-driven and app-enabled intervention called 'the Tshwane Insulin Project intervention'. The Tshwane Insulin Project intervention was designed and evaluated using the framework recommended by the Medical Research Council for complex interventions. The Tshwane Insulin Project intervention was developed in four sequential phases: planning, design, implementation and evaluation. The Tshwane Insulin Project intervention followed the Integrated Chronic Disease Management framework to facilitate implementation and acceptability. The Tshwane Insulin Project comprises a facility-level intervention, where nurses evaluate patients and initiate insulin, an individual-level intervention where community healthcare workers visit patients at their homes to follow-up and provide educational information, while using telehealth to enable physician-directed insulin titration if needed, and a community-level intervention aimed at empowering community healthcare workers to support people living with diabetes and raise awareness of diabetes. Conclusion: The technological advancements in digital health and telemedicine present an opportunity to improve diabetes care in resource-limited countries. This work can inform those intending to develop and implement complex interventions in primary healthcare in developing countries.